(untitled) (Economic and Political Thought, 2018)
The basis of Weber thesis is presented in the work The Protestant Ethic and the Spirit of Capitalism. Analysing the development of capitalism Weber connected it, among others, with an increase of rationality caused by a particular religion. He stated that an increase in ascetic Protestantism (including Calvinism), and in particular a set of values and beliefs about work, savings, investment, and multiplying wealth were essential to the creation of modern capitalism. The author conducted a verification of Weber’s thesis and used his own econometric model for the economy of Germany. The Protestant religion, in addition to the level of emigration, the proportion of people working in agriculture, was important for the creation of social welfare (GDP). This is a negative relationship as an increase in the number of Protestants led to a decrease in GDP growth. At the same time, it should be noted that the percentage of the number of Protestants in the German Reich decreased during the analysed period. The relatively low coefficient of determination also indicates that the model explains 33.13% of the cases.